Highly qualified InP based QDs through a temperature controlled ZnSe shell coating process and their DFT calculations - Seo, Haewoon; Park, Ju Hyun; Kwon, O. Hoon; Kwon, O. Pil; Kwak, Sang Kyu; Kim, Sang Wook (Nanoscale Advances, 2020)
For QDs used in displays, a narrow emission linewidth and emission peak tuning depending on the morphology of the QDs are the most important factors in order to maximize the range of colors to be represented. CdSe-based QDs are known as the most suitable QDs for displays, but cadmium is a highly toxic and regulated substance for use worldwide; InP-based QDs are the most noteworthy alternative. However, InP-based QDs have a wider linewidth of emission light in the entire visible region compared to CdSe-based QDs. In this work, we use the ZnSe inner shell as a lattice buffer layer between the InGaP core and the ZnS outer shell in the type-I structure, using a heating-up method in which ZnSe precursors were added to a low-temperature core solution and then rapidly raised to a temperature of 270-320 °C. Interestingly, when reacting at high temperatures, the shape of the QDs changes to a tetrahedron, and the FWHM becomes narrower than at low temperature. To understand this phenomenon, we proceeded with transmission electron microscopy (TEM) and powder X-ray diffraction (PXRD) analyses, and a reasonable explanation was provided with DFT calculations. This journal is
Keywords: Core solutions; DFT calculation; Emission linewidth; Emission peaks; High temperature; Low temperatures; Powder X-ray diffraction (pXRD); Visible region